Preparation method of capillary electrochromatography open-tube column based on chiral induction covalent organic framework modification, product and application thereof
Patent Information
- Application Number
- CN202611234137.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-11-03
AI Technical Summary
Existing OT-CEC chiral interface coating technology suffers from poor bonding stability and mechanical strength, and it is difficult to balance the selectivity of loading, making it impossible to achieve large-scale mass production. Furthermore, the lack of a clear molecular recognition mechanism limits its industrial application in the field of chiral drug detection.
A method for preparing open capillary electrochromatographic columns modified with chiral-induced covalent organic frameworks was proposed. A continuous and dense COF thin layer was formed by one-step in-situ polymerization on the inner wall of the capillary. L-(+)-tartaric acid was used to simultaneously achieve chiral induction and acid catalysis to form a permanent helical chiral framework, which achieved multiple covalent bonding with the silica substrate. This method solved the problems of uneven coating distribution and bonding stability.
The coating achieves uniform distribution and stability, improves chiral selectivity and loading capacity, maintains stable chiral recognition ability within the range of 30~70 ℃, exhibits excellent thermal stability, is suitable for high-throughput chiral drug detection, provides quantitative theoretical guidance for enantiomeric recognition molecular mechanisms, and is applicable to routine testing in pharmaceutical companies and hospital laboratories.
Smart Images

Figure CN123024529A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of capillary column preparation technology, specifically to the preparation method of open capillary electrochromatographic columns based on chiral-induced covalent organic framework modification, as well as their products and applications. Background Technology
[0002] Although enantiomers of chiral drugs possess identical basic physicochemical properties, their pharmacological activities and toxicological characteristics differ significantly. Typically, a single isomer can exert the expected therapeutic effect, while its mirror-image isomer not only has extremely low biological activity but also readily induces severe toxic side effects. Based on this characteristic of chiral drugs, the precise detection of drug enantiomer purity places extremely high technical demands on fields such as drug quality testing, clinical drug safety, and screening for chiral environmental pollutants.
[0003] Currently, gas chromatography (GC), high-performance liquid chromatography (HPLC), and capillary electrochromatography (CEC) are the mainstream techniques for chiral enantiomer separation and analysis. However, all traditional detection platforms have inherent technical limitations: conventional GC is only suitable for volatile analytes and has a narrow substrate range; conventional HPLC requires a large amount of organic solvent, has a long separation cycle, high detection costs, and its detection efficiency is insufficient to meet the needs of high-throughput screening. CEC combines the electrophoretic mass transfer mechanism with the chromatographic stationary phase retention separation mechanism, possessing advantages such as high column efficiency, extremely low sample consumption, fast separation speed, and low reagent loss, and has great application potential in the fields of high-throughput chiral drug screening and quantitative detection of trace enantiomers.
[0004] Open-tube capillary electrochromatography (OT-CEC), as a mainstream miniaturized CEC technology, effectively avoids the technical challenges of packed column clogging and bubble interference. The chiral separation performance of OT-CEC relies entirely on the functional interface layer covalently fixed to the inner wall of the quartz capillary. Therefore, the structural design and preparation process of the chiral immobilization interface are the core factors determining its chiral separation performance. Leveraging the advantages of electric field-driven mass transfer, OT-CEC can achieve rapid baseline separation of multi-component chiral mixtures in mild water-organic mixtures, adapting to the separation and detection needs of water-soluble chiral drugs, amino acid enantiomers, and chiral pesticide residues. Simultaneously, the micron-scale capillary interface significantly reduces mass transfer resistance and shortens the equilibration time between the stationary and mobile phases, enabling complete separation of chiral enantiomers within approximately 10 minutes. Despite the numerous technological advantages of OT-CEC, current OT-CEC chiral interface coating technology faces three major bottlenecks, severely restricting its transformation from laboratory research to industrial and commercial detection equipment, becoming a major barrier to the industry's technological development. First, the interfacial bonding stability and mechanical strength are poor. Traditional techniques often use physical coating or ex-situ post-modification methods to prepare coatings, where the chiral selector and the quartz substrate are only bonded by weak non-covalent bonds. This easily leads to problems such as coating peeling and unstable electroosmotic flow, resulting in short column life and poor reproducibility between different batches, making large-scale mass production impossible. Second, there is an irreconcilable contradiction between loading capacity and chiral selectivity. Ultrathin coatings can ensure channel permeability and column efficiency, but the number of chiral recognition sites is insufficient, resulting in poor separation. Thickening and densifying the coating can increase the loading capacity, but it will block capillary channels and reduce column separation efficiency, failing to balance adsorption capacity and stereoselectivity. Third, the molecular recognition mechanism is unclear. Existing studies can only verify the separation effect through chromatographic detection data, lacking quantitative theoretical verification and visual evidence. It is impossible to clarify the core mechanism of enantiomer stereodiscrimination, making it difficult to guide the targeted design and optimization of high-performance chiral porous interfacial materials.
[0005] In recent years, crystalline chiral porous framework materials with ordered channels and abundant chiral binding sites have been gradually applied in the field of chiral separation, improving the shortcomings of traditional coating materials to some extent. However, new technical problems still exist when these materials are applied to OT-CEC: the synthesis process of chiral building blocks of traditional crystalline chiral porous framework materials is complex, relying on cumbersome asymmetric catalytic reactions, resulting in extremely high preparation costs and hindering widespread application. Chiral-induced covalent organic frameworks (Chiral-induced COFs) do not require the pre-synthesis of chiral monomers and can form intrinsic helical framework structures through asymmetric induction, making them a promising new type of chiral porous interface material. However, there is currently no in-situ interface preparation process based on Chiral-induced COFs, making it impossible to achieve stable covalent bonding between the coating and the capillary substrate. Furthermore, the industry pain point of difficulty in balancing loading capacity, selectivity, and stability in existing technologies remains unresolved. At the same time, the lack of a comprehensive theoretical framework to explain its chiral recognition mechanism greatly limits the industrial application of OT-CEC technology in the field of chiral drug detection. Summary of the Invention
[0006] Purpose of the invention: The first objective of this invention is to provide a method for preparing a capillary electrochromatographic open column based on chiral-induced covalent organic framework modification.
[0007] The second objective of this invention is to provide a capillary electrochromatographic open column based on chiral-induced covalent organic frame modification.
[0008] The final objective of this invention is to provide an application of a chiral-induced covalent organic frame-modified capillary electrochromatographic open column in the separation of chiral drug molecules.
[0009] Technical Solution: To achieve the above objectives, this invention provides a method for preparing a capillary electrochromatographic open column based on chiral-induced covalent organic framework modification, comprising the following steps:
[0010] (1) A fused silica capillary was sequentially passed through sodium hydroxide solution and hydrochloric acid solution to obtain a capillary with exposed silanol groups on the tube wall; 3-aminopropyltriethoxysilane solution was injected into the silanol-exposed capillary and sealed and incubated at a constant temperature to obtain a capillary with amino-modified tube wall; glutaraldehyde aqueous solution was injected into the amino-modified capillary and reacted at room temperature to obtain a capillary with spacer arms covalently connected to the tube wall.
[0011] (2) Dissolve terephthalaldehyde and tetra(4-aminophenyl)methane in a solvent and sonicate to obtain a reaction system; mix the reaction system with an aqueous solution of L-(+)-tartaric acid, and quickly pump the mixture into a capillary tube covalently connected with a spacer arm. Seal and keep the reaction at a constant temperature; after the reaction is completed, cool to room temperature, rinse the capillary tube with acetonitrile, and dry it with high-purity nitrogen to obtain the open capillary electrochromatographic column.
[0012] Preferably, the molar ratio of terephthalaldehyde to the tetra(4-aminophenyl)methane is 2:3.
[0013] Preferably, the solvent includes any one of 1,4-dioxane, DMF, and DMSO, more preferably 1,4-dioxane.
[0014] Preferably, the L-(+)-tartaric acid aqueous solution is a chiral dopant and an acid catalyst.
[0015] Preferably, the ratio of the molar number of carboxyl groups of tartaric acid to the molar number of amino groups of tetrakis(4-aminophenyl)methane in the L-(+)-tartaric acid aqueous solution is 1:5~10.
[0016] Preferably, the sealed and constant-temperature reaction time is 4 to 8 days, more preferably 4 days.
[0017] Preferably, the constant temperature is 80 ℃.
[0018] Preferably, the sodium hydroxide solution has a concentration of 1 mol / L, the hydrochloric acid solution has a concentration of 0.1 mol / L, the 3-aminopropyltriethoxysilane methanol solution has a concentration of 50% (volume ratio), and the glutaraldehyde aqueous solution has a pH of 11.
[0019] This invention also provides the application of a capillary electrochromatographic open column based on chiral induction covalent organic frame modification in the separation of chiral drug molecules, wherein the chiral drug molecules include one or more of amlodipine, propranolol, metoprolol, chlorpheniramine, clenbuterol, terbutaline, verapamil, and isoproterenol.
[0020] Preferably, it includes the following steps:
[0021] (1) Install the capillary electrochromatographic open column in the electrophoresis instrument and connect one end to the ultraviolet detector to complete the installation;
[0022] (2) After installation, rinse the activated capillary with running buffer;
[0023] (3) The chiral drug molecule to be tested is dissolved in a water-methanol mixture and introduced into an activated capillary. After injection, separation is achieved by applying a separation voltage. The ultraviolet detector captures the absorbance signal and generates an electrophoresis pattern in real time, thereby realizing the separation and detection of chiral drug molecules.
[0024] Preferably, the running buffer comprises a 5-15 mM phosphate buffer solution containing 50%-60% acetonitrile, the pH of which is 9-10; the water-methanol mixture has a water-to-methanol volume ratio of 1:1; and the final concentration of the chiral drug is 0.1-0.9 mg / mL. -1The separation voltage is 5~15 kV; the injection height is 5~10 cm, and the injection time is 2~9 s; the capillary column temperature is kept constant at 20~30 ℃ throughout the separation and detection process.
[0025] Preferably, the detection wavelength is 210-230 nm;
[0026] More preferably, the running buffer is a 10 mM phosphate buffer solution containing 55% acetonitrile, with the pH adjusted to 9.5; the separation voltage is set to 10 kV; the sample is injected using hydrodynamics, and the final concentration of the chiral drug is 0.5 mg / mL. -1 The injection height was 10 cm, the injection time was 5 s, the detection wavelength was 220 nm, and the capillary column temperature was kept constant at 25 ℃ throughout the separation and detection process.
[0027] Beneficial effects: Compared with the prior art, the advantages of the present invention are as follows:
[0028] (1) This invention does not require the prior synthesis of expensive chiral monomers. Instead, it uses inexpensive L-(+)-tartaric acid to simultaneously achieve chiral induction and acid catalysis. By relying on the chiral memory effect, the achiral COF skeleton is transformed into a permanent helical chirality, which greatly simplifies the preparation process and reduces the cost of raw materials.
[0029] (2) This invention forms a continuous and dense COF thin layer through one-step in-situ polymerization on the inner wall of a capillary, which is then covalently bonded to a silica substrate. The scanning electron microscope image of the capillary cross section clearly shows that the chiral induced COF (Λ)-TAPM-TPA coating is uniformly and continuously immobilized on the inner wall of the capillary. The coating thickness in different sections of the same chromatographic column is stable at 250~355 nm, with no obvious agglomeration, peeling, or uneven coverage. Energy dispersive X-ray spectroscopy (EDS) elemental mapping further confirms that carbon, nitrogen, and oxygen elements are uniformly distributed throughout the coating. The in-situ growth strategy completely solves the long-standing problem of uneven distribution of chiral selectors in traditional open columns.
[0030] (3) The gradient temperature adsorption test of the present invention shows that the chiral recognition ability of the material is stable in the range of 30~70 ℃; the thermogravimetric-derivative thermogravimetric (TGA / DTG) test shows that the material has excellent thermal stability below 400 ℃: mass loss of 14.85% (removal of adsorbed impurities) at 25~200 ℃, slight weight loss of 2.57% at 200~400 ℃ (decomposition of functional groups); pH gradient adsorption experiment shows that the enantioselectivity of the material continues to improve from neutral to alkaline environment, and the performance is optimal at pH=9.5; in 5 adsorption-regeneration cycle tests, the enantiomeric excess value is stable at about 23.74%, and the saturated adsorption capacity QL≈4.2 mg / g; the reaction temperature does not exceed 80 ℃ throughout the process, there are no high temperature and strong corrosion steps, it will not destroy the COF helical chiral framework, the equipment requirements are low, and it can be prepared in batches on a large scale;
[0031] (4) This invention can baseline separate eight clinical chiral drugs with large structural differences, including amlodipine, propranolol, metoprolol, chlorpheniramine, clenbuterol, terbutaline, verapamil, and isoproterenol. The separation effect is not diminished after 50 consecutive injections, and it is suitable for routine testing in pharmaceutical companies and hospital laboratories.
[0032] (5) The DFT quantization calculation of this invention intuitively reveals the enantiomeric recognition molecular mechanism, providing general theoretical guidance for the directional design of high-performance chiral porous interface materials. Attached Figure Description
[0033] Figure 1 Schematic diagram of L-(+)-tartaric acid-induced (Λ)-TAPM-TPA COF synthesis; Figure 2 Schematic diagram of (Λ)-TAPM-TPA COF@capillary column synthesis; Figure 3 A comparison of the enantioselective adsorption performance of COF under different reaction times, inducer ratios, and solvents; Figure 3 In this context, 'a' represents the enantioselective adsorption capacity at different reaction times. Figure 3 In this context, b represents the enantioselective adsorption capacity of TAPM-TPA, 1:5 chiral induced COF(Δ)-TAPM-TPA, and 1:10 chiral induced COF(Λ)-TAPM-TPA; Figure 3 In this context, 'c' represents the enantioselective adsorption capacity in different solvent systems. Figure 4 The CD spectrum, microstructure, PXRD, and FTIR structural characterization diagrams of COF are shown. Figure 4 In the image, 'a' represents the circular dichroism chromatogram of the chiral-induced covalent organic framework (Λ)-TAPM-TPA. Figure 4 b and c in the figure are scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the surface microstructure of the chiral induced covalent organic framework (Λ)-TAPM-TPA. Figure 4 In the diagram, d represents the powder X-ray diffraction pattern of the chiral-induced covalent organic framework (Λ)-TAPM-TPA; Figure 4 In the figure, 'e' represents the Fourier transform infrared spectral characteristics of the chiral induced covalent organic framework (Λ)-TAPM-TPA. Figure 5 A comparison of fine XPS elemental spectra of chiral / chiral COFs; Figure 5 In the figure, 'a' represents the XPS full spectrum of COF TAPM-TPA and chiral-induced COF (Λ)-TAPM-TPA; Figure 5 b in the spectrum represents the C 1s high-resolution spectrum; Figure 5 c in the spectrum represents the N 1s high-resolution spectrum; Figure 5In this context, d represents the O 1s high-resolution spectrum; Figure 6 The graph shows the test results for COF thermal stability, pH tolerance, cyclic adsorption, and long-term storage stability. Figure 6 In this context, 'a' represents the effect of temperature on the chiral-induced selective adsorption and separation performance of COF(Λ)-TAPM-TPA for tryptophan; Figure 6 In the figure, b represents the TGA and DTG curves of the chiral-induced thermal stability of COF(Λ)-TAPM-TPA; Figure 6 In this context, 'c' represents the effect of pH on the chiral-induced selective adsorption and separation performance of COF(Λ)-TAPM-TPA for tryptophan; Figure 6 In this context, d represents the enantioselective adsorption capacity of chiral-induced COF(Λ)-TAPM-TPA under five cycles. Figure 6 In this context, 'e' represents the effect of long-term storage on the selective adsorption and separation performance of tryptophan by chiral-induced COF(Λ)-TAPM-TPA. Figure 7 To modify the SEM morphology and EDS elemental distribution of the inner wall of the capillary; among which Figure 7 In the image, a and b are SEM images of chiral-induced COF(Λ)-TAPM-TPA@capillary at different magnifications; Figure 7 c and d in the image are SEM images of other regions of the same chiral-induced COF(Λ)-TAPM-TPA@capillary at different magnifications; Figure 7 In the figure, 'e' represents the EDS elemental distribution map of the chiral-induced C, N, and O elements on the inner wall of the capillary. Figure 8 Electrochromatographic separation spectra of 8 chiral drugs; Figure 9 Electrochromatograms of the 1st, 10th, 15th, 20th, and 50th consecutive separations of R / S-amlodipine enantiomers; Figure 10 A schematic diagram illustrating the growth mechanism of the COF helical backbone induced by chiral memory; Figure 11 This is the electrostatic potential diagram of the enantiomer-COF complex obtained from DFT calculation; where Figure 11 In the diagram, 'a' represents the electrostatic potential distribution of R-amlodipine / chiral induced COF(Λ)-TAPM-TPA. Figure 11 In the diagram, b represents the electrostatic potential distribution of S-amlodipine / chiral induced COF(Λ)-TAPM-TPA; Figure 12The results are for IMH analysis; R-Amlodipine / (Λ)-TAPM-TPA represents the IMH analysis results of R-amlodipine / chiral-induced COF (Λ)-TAPM-TPA, and S-Amlodipine / (Λ)-TAPM-TPA represents the IMH analysis results of S-amlodipine / chiral-induced COF (Λ)-TAPM-TPA. Figure 13 The figures are scatter plots of IMH; where R-Amlodipine / (Λ)-TAPM-TPA is the scatter plot of IMH for R-Amlodipine / chiral-induced COF (Λ)-TAPM-TPA, and S-Amlodipine / (Λ)-TAPM-TPA is the scatter plot of IMH for S-Amlodipine / chiral-induced COF (Λ)-TAPM-TPA. Detailed Implementation
[0034] The technical solution provided by the present invention will be described in detail below with reference to the embodiments. Unless otherwise specified, the experimental methods in the following embodiments are conventional methods. Unless otherwise specified, the experimental materials used in the following embodiments were all purchased from conventional biochemical reagent stores.
[0035] The reagents used in the examples are as follows:
[0036] Tetra(4-aminophenyl)methane (TAPM) (Catalog No.: 011192759), terephthalaldehyde (TPA, Catalog No.: 01119275), propranolol (Catalog No.: 01119276), clenbuterol (Catalog No.: 01119277), terbutaline (Catalog No.: 01119278), verapamil (Catalog No.: 01119279), amlodipine (Catalog No.: 01119280), chlorpheniramine maleate (Catalog No.: 01119281), metoprolol (Catalog No.: 01119282), isoproterenol (Catalog No.: 01119283), and L-(+)-tartaric acid (Catalog No.: 01121231) were all purchased from Shanghai Titan Technology Co., Ltd., China. 1,4-Dioxane (item number: 01014417) was purchased from Shanghai Maclean Biotechnology Co., Ltd., China.
[0037] The UV-transmitting fused silica capillary tube (75 μm inner diameter, 365 μm outer diameter) was purchased from Ruifeng Chromatography Instruments Co., Ltd., Yongnian County, Handan, China. Deionized water was used throughout the entire experiment.
[0038] The instruments used in this example are as follows:
[0039] CEC experiments were conducted using a CL1030 capillary electrophoresis system manufactured by Beijing Huayang Limin Instrument Co., Ltd., equipped with a 190–700 nm ultraviolet detector and a 30 kV high-voltage power supply. The potassium bromide pellet method was employed, and Fourier transform infrared spectroscopy was performed using a Nicolet Magna-560 Fourier transform infrared spectrometer located in Madison, Wisconsin, USA, at a wavelength of 4000–400 cm⁻¹. -1 Fourier transform infrared (FTIR) spectra were measured within the wavenumber range for COF material structure characterization. Thermogravimetric analysis (TGA) was performed using a PerkinElmer TGA4000 thermogravimetric analyzer under air oxidizing atmosphere and nitrogen protective atmosphere, with a heating rate of 5 °C / min and a test temperature range of 30–800 °C. Powder X-ray diffraction (PXRD) data were acquired using a Bruker D8 Advance X-ray diffractometer with copper target Kα rays as the radiation source. Elemental surface distribution analysis (SEM) and energy-dispersive X-ray spectroscopy (EDS) were performed on a Zeiss Sigma 500 field emission scanning electron microscope. Circular dichroism (CD) analysis was performed using a Jasco J-1500 circular dichroism chromatograph. Transmission electron microscopy (TEM) characterization was performed using a JEOL JEM-2100F field emission transmission electron microscope with an accelerating voltage of 200 kV.
[0040] Example 1: Synthesis of Chiral Induced Covalent Organic Frameworks
[0041] 1. Optimization of synthetic conditions for chiral-induced covalent organic frameworks (COF(Λ)-TAPM-TPA)
[0042] (1) Optimization of reaction time
[0043] Synthesize COF(Λ)-TAPM-TPA according to the following steps:
[0044] S1: Add 36.0 mg (0.3 mmol) terephthalaldehyde (TPA) and 60.0 mg (0.2 mmol) tetrakis(4-aminophenyl)methane (TAPM) to a polytetrafluoroethylene-lined pressure-resistant reaction tube, then add 9 mL of anhydrous 1,4-dioxane, and sonicate until the raw materials are completely dissolved to obtain the reaction system.
[0045] S2: Prepare an L-(+)-tartaric acid aqueous solution such that the molar ratio of the carboxyl group of tartaric acid to the molar ratio of the amino group of TAPM is 1:5. Take 0.6 mL of L-(+)-tartaric acid aqueous solution as a chiral dopant and acid catalyst and add it to the reaction system. Immediately seal the reaction tube.
[0046] S3: After reacting at 80 ℃ for 1, 2, 4, 6 and 8 days respectively, a yellow precipitate was formed in the system. The precipitate was filtered, washed repeatedly with anhydrous ethanol, and dried under vacuum at 80 ℃ for 12 h to obtain chiral induced COF powder (Λ)-TAPM-TPA.
[0047] Synthesis diagram as shown Figure 1 As shown. To maximize the stereorecognition capability of (Λ)-TAPM-TPA, this invention detects the enantiomeric excess value (ee%) and the enantioselective adsorption capacity (Q). The specific steps are as follows:
[0048] L / D tryptophan was dissolved in 10 mmol / L phosphate buffer at pH 9.5 to prepare a 200 mg / L stock solution; then diluted with phosphate buffer to prepare a 20 mg / L L / D tryptophan standard solution.
[0049] Two mg of chiral induced COF(Λ)-TAPM-TPA was weighed and reacted at 80 °C for 1, 2, 4, 6, and 8 days, respectively, in test tubes. Two mL of phosphate buffer solution was added to the blank group, and two mL of 20 mg / L D-tryptophan and L-tryptophan solutions were added to the experimental groups, respectively. The tubes were placed in a shaker and incubated at 30 °C and 150 rpm for 1 h for adsorption, followed by filtration through a 0.45 μm filter membrane.
[0050] The adsorption capacity (Q) of tryptophan for chiral-induced COF (Λ)-TAPM-TPA is calculated according to the following formula:
[0051]
[0052] In the formula: C0 is the initial concentration of tryptophan solution before adsorption (mg / L); C e V represents the equilibrium concentration of tryptophan solution after 1 h of adsorption (mg / L); V is the volume of solution used in the adsorption experiment (L); and m is the mass of adsorbent (g).
[0053] The enantiomeric excess (ee%) is used to evaluate the selective adsorption capacity of a material for tryptophan with different configurations. A higher ee% indicates stronger chiral recognition performance. ee% is calculated using the following formula:
[0054]
[0055] In the formula: This represents the amount of L-tryptophan adsorbed by the adsorbent. The adsorption capacity (mg / g) of the adsorbent for D-tryptophan.
[0056] The results are as follows Figure 3 As shown in a, the optimal reaction time is determined to be 4 days.
[0057] (2) Optimization of the molar ratio of L-(+)-tartaric acid aqueous solution
[0058] Synthesize COF(Λ)-TAPM-TPA according to the following steps:
[0059] S1: Add 36.0 mg (0.3 mmol) terephthalaldehyde (TPA) and 60.0 mg (0.2 mmol) tetrakis(4-aminophenyl)methane (TAPM) to a polytetrafluoroethylene-lined pressure-resistant reaction tube, then add 9 mL of anhydrous 1,4-dioxane, and sonicate until the raw materials are completely dissolved to obtain the reaction system.
[0060] S2: Prepare L-(+)-tartaric acid aqueous solutions with different molar ratios, such that the ratio of the molar number of carboxyl groups in tartaric acid to the molar number of amino groups in TAPM is 1:1, 1:5, 1:10, and 1:20. Take 0.6 mL of L-(+)-tartaric acid aqueous solution as a chiral dopant and acid catalyst and add it to the reaction system. Immediately seal the reaction tube.
[0061] S3: After reacting at a constant temperature of 80 ℃ for 4 days, a yellow precipitate was formed in the system. The precipitate was filtered, washed repeatedly with anhydrous ethanol, and dried under vacuum at 80 ℃ for 12 h to obtain chiral induced COF powder (Λ)-TAPM-TPA.
[0062] In this system, L-(+)-tartaric acid is the sole chiral source, and its dosage balances the crystallinity and helical twist of the framework. Enantiomeric excess (ee%) and enantioselective adsorption capacity (Q) were determined for tartaric acid carboxyl to TAPM amino molar ratios of 1:1, 1:5, 1:10, and 1:20, as well as for a chiral TAPM-TPA control (where the amino group in TAPM is 1:0 compared to the carboxyl group in L-(+)-tartaric acid, i.e., no L-(+)-tartaric acid was added during preparation). The results are as follows: Figure 3 As shown in b, no crystalline COF precipitate was formed at ratios of 1:1 and 1:20; (Λ)-TAPM-TPA powder with good crystallinity and excellent chiral recognition performance was obtained at ratios of 1:5 and 1:10; the chiral TAPM-TPA control (1:0) showed that its adsorption amounts for L-tryptophan and D-tryptophan were almost the same, directly proving that the stereodiscrimination ability came entirely from the tartaric acid-induced distortion of the COF skeleton, rather than the interaction between monomers.
[0063] (3) Solvent optimization
[0064] Synthesize COF(Λ)-TAPM-TPA according to the following steps:
[0065] S1: Add 36.0 mg (0.3 mmol) terephthalaldehyde (TPA) and 60.0 mg (0.2 mmol) tetrakis(4-aminophenyl)methane (TAPM) to a polytetrafluoroethylene-lined pressure-resistant reaction tube, then add 9 mL of mesitylene (MS), mesitylene:1,4-dioxane (1:1), 1,4-dioxane, N,N-dimethylformamide (DMF), and dimethyl sulfoxide (DMSO) and sonicate until the raw materials are completely dissolved.
[0066] S2: Prepare an aqueous solution of L-(+)-tartaric acid (the molar ratio of tartaric acid carboxyl groups to TAPM amino groups is 1:10), take 0.6 mL as a chiral dopant and acid catalyst and add it to the reaction system, and immediately seal the reaction tube.
[0067] S3: After reacting at a constant temperature of 80 ℃ for 4 days, a yellow precipitate was formed in the system. The precipitate was filtered, washed repeatedly with anhydrous ethanol, and dried under vacuum at 80 ℃ for 12 h to obtain chiral induced COF powder (Λ)-TAPM-TPA.
[0068] The enantiomeric excess (ee%) and enantioselective adsorption capacity (Q) of COF(Λ)-TAPM-TPA synthesized with different types of solvents were determined, and the results are as follows: Figure 3 As shown in c, anhydrous 1,4-dioxane is the optimal reaction medium, which can promote the assembly of ordered chiral frameworks and improve chiral recognition performance.
[0069] In summary, the optimal one-pot synthesis conditions of this invention are as follows: 36.0 mg TPA and 60.0 mg TAPM are dissolved in 9 mL of anhydrous 1,4-dioxane and sonicated; 0.6 mL of L-(+)-tartaric acid inducer aqueous solution (the molar ratio of tartaric acid carboxyl groups to TAPM amino groups is 1:5) is added dropwise under stirring, and the mixture is heated at 80 °C for 4 days to obtain crystalline chiral induced COF(Λ)-TAPM-TPA.
[0070] 2. Verification of the successful construction of chiral-induced covalent organic frameworks
[0071] COF(Λ)-TAPM-TPA was synthesized under the above-described optimal synthesis conditions, and control TAPM-TPA COF was synthesized according to the above-described chiral TAPM-TPA synthesis steps.
[0072] The intrinsic chirality of the material was successfully constructed using circular dichroism (CD) chromatography, as demonstrated by the successful construction. Figure 4As shown in Figure a, the chiral TAPM-TPA COF exhibits no CD signal, while COF(Λ)-TAPM-TPA shows a significant negative Cotton effect at 450 nm, directly confirming the chiral-induced formation of a helical framework. Combined with subsequent chiral resolution results, this chiral optical response demonstrates the successful fabrication of a stereopore chiral COF material.
[0073] The microstructure of chiral-induced COF(Λ)-TAPM-TPA was observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM): the chiral-induced COF(Λ)-TAPM-TPA exhibited a uniform spindle-shaped microcrystal morphology (e.g., Figure 4 (as shown in b and c).
[0074] Using Materials Studio 7.0 software and powder X-ray diffraction (PXRD) to refine lattice parameters, a (Λ)-TAPM-TPA unit cell model was constructed. The experimental PXRD spectra showed low Pawley refined residual factors (Rwp=9.19%, Rp=6.51%), demonstrating the high crystallinity of the synthesized COF (e.g., ...). Figure 4 (as shown in d); the characteristic diffraction peaks at 8.95°, 12.6°, 14°, 16.8°, 18°, 19°, 20.2°, 21.1°, 24.7°, 29.3°, and 30.5° correspond to the (200), (220), (211), (301), (400), (321), (420), (411), (501), (422), and (611) crystal planes, respectively; the simulated overlapping and twisted spiral stacking differ only in the intensity and width of the diffraction peaks.
[0075] Fourier transform infrared spectroscopy (FTIR) confirmed complete Schiff base condensation with no residual free tartaric acid inducer (e.g. Figure 4 (as shown in e): All COF samples were at 1616 cm⁻¹. -1 The characteristic imine stretching vibration peak appears, with the monomeric amino group (3394 cm⁻¹). -1 ), aldehyde group (1695 cm) -1 The vibration peak almost completely disappeared; there was no 1741 cm peak. -1 The characteristic peak of the tartaric acid carboxyl group excludes the use of physically adsorbed free inducers. The infrared spectra of samples with inducer ratios of 1:0, 1:5, and 1:10 show high overlap, proving that chiral induction only regulates skeletal torsion and does not change the imine-bonded COF backbone structure.
[0076] X-ray photoelectron spectroscopy (XPS) was used to analyze the surface elemental composition and electronic states (e.g., Figure 5 As shown). Among them, the full spectrum (such as...) Figure 5As shown in (a) in the figure, the chiral COF TAPM-TPA and the chiral-induced COF (Λ)-TAPM-TPA contain only C, N, and O elements, indicating that no impurities are introduced during the chiral induction process. High-resolution C 1s, N 1s, and O 1s spectra (as shown in the figure) Figure 5 As shown in bd in the figure, both materials have fully formed imine bonds; the chiral-induced COF (Λ)-TAPM-TPA has a higher signal intensity of oxygen-containing functional groups and a slight shift in the N-containing characteristic peak, which is due to the electron redistribution caused by tartaric acid fragments embedded in the twisted chiral framework, further confirming that the chiral induction unit has been successfully integrated into the COF framework.
[0077] 3. Evaluation of the thermal stability, pH stability, cyclic regeneration stability, and long-term storage stability of chiral induced COF (Λ)-TAPM-TPA.
[0078] Practical chromatographic separation applications place stringent requirements on the structural and functional stability of materials. This embodiment evaluates the thermal stability, pH stability, cyclic regeneration stability, and long-term storage stability of (Λ)-TAPM-TPA using an enantioselective adsorption index system.
[0079] (1) Gradient temperature adsorption test: 2 mg of COF(Λ)-TAPM-TPA induced by the chirality of L-(+)-tartaric acid (the ratio of the molar number of carboxyl groups of tartaric acid to the molar number of amino groups of TAPM is 1:5) was weighed and placed in test tubes; 2 mL of phosphate buffer solution was added to the blank group, and 2 mL of D-tryptophan and L-tryptophan solution with a concentration of 20 mg / L were added to the experimental group respectively; the tubes were placed in a shaker and shaken at 150 rpm for 1 h at 30°C, 40°C, 50°C, 60°C and 70°C respectively. Then, the tubes were filtered with a 0.45 μm filter membrane, and the enantiomeric excess value (ee%) and enantioselective adsorption capacity (Q) were detected.
[0080] like Figure 6 As shown in a, gradient temperature adsorption tests show that the material's chiral recognition ability is stable within the range of 30~70 ℃.
[0081] (2) Thermogravimetric-Dimer-Dimer Thermogravimetric (TGA / DTG) Test: Thermogravimetric analysis (TGA) and derivative thermogravimetric analysis (DTG) were performed (test temperature range 30~800℃). The results are as follows: Figure 6 As shown in b, thermogravimetric-micro-quotient thermogravimetric (TGA / DTG) tests show that the material has excellent thermal stability below 400℃: 14.85% mass loss at 25~200℃ (removal of adsorbed impurities), slight weight loss of 2.57% at 200~400℃ (decomposition of functional groups), decomposition of the main skeleton at 400~600℃ with a total weight loss of 85.44%, and complete decomposition above 600℃.
[0082] (3) pH gradient adsorption experiment: L / D tryptophan was dissolved in phosphate buffer with pH values of 7.5, 8.5, 9.5, 10.5, 11.5 and a concentration of 10 mmol / L to prepare a 200 mg / L stock solution; then it was diluted with phosphate buffer to prepare a 20 mg / L L / D tryptophan standard solution.
[0083] 2 mg of L-(+)-tartaric acid (the ratio of the molar number of tartaric acid carboxyl groups to the molar number of TAPM amino groups was 1:5) chiral-induced COF(Λ)-TAPM-TPA was weighed and placed in test tubes. 2 mL of phosphate buffer solution was added to the blank group, and 2 mL of D-tryptophan and L-tryptophan solutions with a concentration of 20 mg / L were added to the experimental groups, respectively. The tubes were placed in a shaker and the adsorption was carried out at 30℃ and 150 rpm for 1 h. The tubes were then filtered through a 0.45 μm filter membrane, and the enantiomeric excess value (ee%) and enantioselective adsorption capacity (Q) were measured.
[0084] like Figure 6 As shown in c, pH gradient adsorption experiments show that the enantioselectivity of the material continuously improves from neutral to alkaline environments, with the best performance at pH=9.5; under strongly alkaline conditions, the electrostatic shielding effect weakens the stereospecific binding sites and the chiral recognition ability decreases.
[0085] (4) Adsorption-regeneration cycle test: L / D tryptophan was dissolved in phosphate buffer at pH 9.5 and a concentration of 10 mmol / L to prepare a stock solution of 200 mg / L; then diluted with phosphate buffer to prepare a standard solution of L / D tryptophan with a concentration of 20 mg / L.
[0086] Two mg of L-(+)-tartaric acid (with a tartaric acid carboxyl group to TAPM amino group molar ratio of 1:5) chiral-induced COF(Λ)-TAPM-TPA was weighed out for cycles 0, 1, 2, 3, and 4, respectively, and placed in test tubes. Two mL of phosphate buffer solution was added to the blank group, and two mL of 20 mg / L D-tryptophan and L-tryptophan solutions were added to the experimental groups, respectively. The tubes were placed in a shaker and incubated at 30°C and 150 rpm for 1 h for adsorption. The adsorption was then filtered through a 0.45 μm membrane, and the enantiomeric excess (ee%) and enantioselective adsorption capacity (Q) were measured.
[0087] like Figure 6 As shown in d, during the 5 adsorption-regeneration cycle tests, the enantiomeric excess value remained stable at around 23.74%, and the saturated adsorption capacity QL≈4.2 mg / g, indicating that the material has excellent recycling performance.
[0088] (5) Long-term storage test: L / D tryptophan was dissolved in phosphate buffer at pH 9.5 and a concentration of 10 mmol / L to prepare a stock solution of 200 mg / L; then diluted with phosphate buffer to prepare a standard solution of L / D tryptophan with a concentration of 20 mg / L.
[0089] Two mg of L-(+)-tartaric acid (with a tartaric acid carboxyl group to TAPM amino group molar ratio of 1:5) chiral-induced COF(Λ)-TAPM-TPA, stored for 0, 7, 14, and 21 days respectively, were weighed and placed in test tubes. For the blank group, 2 mL of phosphate buffer solution was added, and for the experimental groups, 2 mL of 20 mg / L D-tryptophan and L-tryptophan solutions were added respectively. The tubes were placed in a shaker and incubated at 30°C and 150 rpm for 1 h for adsorption. The adsorption was then filtered through a 0.45 μm membrane, and the enantiomeric excess (ee%) and enantioselective adsorption capacity (Q) were measured.
[0090] like Figure 6 As shown in e, the enantioselective adsorption index fluctuated very little during long-term storage tests (7, 14, and 21 days), indicating that the chiral porous material has good storage stability.
[0091] Example 2: A capillary electrochromatographic open column based on chiral-induced covalent organic framework modification
[0092] 1. Preparation of open capillary electrochromatographic columns modified with chiral-induced covalent organic frameworks
[0093] The preparation steps are as follows:
[0094] S1: Pretreatment and amination modification of the inner wall of quartz capillary tubes.
[0095] (1) Take a fused silica capillary tube and sequentially pass it through a sodium hydroxide solution with a final concentration of 1 mol / L, a hydrochloric acid solution with a final concentration of 0.1 mol / L, and ultrapure water to rinse it, removing impurities from the tube wall and exposing the silanol groups;
[0096] (2) Inject 50% (volume ratio) 3-aminopropyltriethoxysilane (APTES) methanol solution into the capillary and incubate at 55 °C for 12 h to allow the silanol groups on the inner wall of the capillary to undergo silanization reaction with APTES, thus completing the amino modification of the capillary wall.
[0097] (3) Rinse the capillary tube with ultrapure water to remove unreacted APTES, and dry it with nitrogen for later use.
[0098] S2: Construction of cross-linked spacer layer on the inner wall of capillary.
[0099] Prepare a 2% (volume ratio) glutaraldehyde aqueous solution with pH=11, inject it into an aminated capillary, and react at room temperature. The aldehyde groups at both ends of the glutaraldehyde undergo Schiff base crosslinking with the amino groups on the capillary wall and the amino groups of the subsequent COF monomer, respectively, introducing covalently linked spacer arms into the inner wall of the capillary. Rinse to remove free glutaraldehyde and dry with nitrogen.
[0100] S3: In-situ one-pot chiral-induced COF coating growth.
[0101] (1) Preparation of monomer stock solution: Tetra(4-aminophenyl)methane (TAPM) and terephthalaldehyde (TPA) were dissolved in anhydrous 1,4-dioxane at a molar ratio of 0.2:0.3 to prepare a monomer stock solution with a concentration of 2 mg / mL, and then completely dissolved by sonication.
[0102] (2) Preparation of chiral-induced catalytic system: Prepare an L-(+)- tartaric acid aqueous solution with a molar ratio of 1:10 of the carboxyl group of tartaric acid to the amino group of TAPM as a chiral inducer and acid catalyst;
[0103] (3) In-situ polymerization reaction: Mix the monomer mother liquor with L-(+)-tartaric acid aqueous solution evenly, and quickly pump it into the capillary modified by glutaraldehyde crosslinking, and seal both ends; place it in an 80 ℃ oven for constant temperature reaction for 4 days;
[0104] S4: Post-treatment of capillary columns.
[0105] After the reaction was completed and cooled to room temperature, the capillary was rinsed with acetonitrile to remove unreacted monomers, free inducers and amorphous byproducts. The column was dried with high-purity nitrogen and stored in a nitrogen atmosphere in the dark to obtain a chiral-induced covalent organic framework modified capillary electrochromatographic open column.
[0106] The synthesis process is as follows: Figure 2 As shown. During the reaction, L-(+)-tartaric acid binds to TAPM through reversible imine bonds, generating chiral steric hindrance. Relying on the chiral memory effect, it induces the achiral TAPM-TPA backbone to form an intrinsic helical chiral structure. At the same time, the monomer undergoes covalent Schiff base polymerization on the glutaraldehyde spacer layer on the inner wall of the capillary, generating in situ a continuous and uniform (Λ)-TAPM-TPA COF thin layer with a thickness of 250~355 nm that is covalently bonded to the capillary wall.
[0107] 2. Verify the electrochromatographic chiral separation performance of the capillary column.
[0108] Scanning electron microscopy (SEM) characterization of the capillary inner wall microstructure confirmed that the target composite material was densely deposited on the capillary wall; SEM image of the capillary cross-section (e.g.) Figure 7As shown in the figure (ad), the chiral induced COF (Λ)-TAPM-TPA coating is clearly displayed as uniformly and continuously immobilized on the inner wall of the capillary. The coating thickness in different sections of the same column is stable at 250~355 nm, with no obvious agglomeration, peeling, or uneven coverage. A uniformly distributed COF stationary phase was successfully prepared.
[0109] Energy dispersive X-ray spectroscopy (EDS) elemental mapping (such as...) Figure 7 (e) further confirms that carbon, nitrogen, and oxygen elements are uniformly distributed throughout the coating, and the in-situ growth strategy completely solves the long-standing problem of uneven distribution of chiral selectors in traditional open-column systems.
[0110] Example 3: Application of chiral-induced covalent organic framework-modified capillary electrochromatographic open column in the recognition of chiral drug molecules.
[0111] Eight commonly used chiral beta-blockers and antihistamines were isolated, including amlodipine, propranolol, metoprolol, chlorpheniramine, clenbuterol, terbutaline, verapamil, and isoproterenol. The racemic mixtures of these eight chiral drugs were dissolved separately in a water-methanol (1:1, v / v) mixture to prepare solutions with a concentration of 0.5 mg / mL. -1The preparation temperature was 25 ℃. This experiment used a CL1030 high-performance capillary electrophoresis system purchased from Beijing Huayang Limin Instrument Co., Ltd. The fused silica capillary was coiled and fixed within the support coil of the electrophoresis unit. The anode sample inlet of the capillary was connected to the top pressure flushing module, and the other end, after the coating was removed, passed through the flow cell window built into the CL1030 independent UV detector, finally penetrating into the cathode waste bottle to form a complete pathway. The detection wavelength was set by the CL1030 UV detector (wavelength adjustable range 190~700 nm) and its accompanying workstation software, 0~30 nm. The kV DC high voltage for separation is provided by an external CL101A series high-voltage power supply. The running buffer is contained in the anode sample bottle and the cathode waste bottle, respectively, immersing both platinum electrodes to establish a closed electric field loop and filling the capillary lumen throughout the process as the background electrolyte and solute migration medium for electrophoretic separation. The complete separation operation procedure is as follows: turn on the CL1030 UV detector, CL101A high-voltage power supply and computer workstation in sequence; after the deuterium lamp is fully preheated, the capillary is installed; and the instrument pressurization system sequentially applies acid and alkali solutions, ultrapure water and degassing solution. After equilibration, the run buffer was used to rinse and activate the capillary. The buffer bottle and the sample bottle were placed in the corresponding positions on the lifting tray. The detection wavelength, separation voltage, electric / differential injection parameters, and post-rinsing program were entered into the workstation. After sample injection, a high-voltage electric field was applied. Analytes with different charge-to-mass ratios separated sequentially in the buffer system within the capillary due to differences in force. They flowed through the UV detection window, where the absorbance signal was captured by the detector, generating an electrophoresis pattern in real time. After the experiment, the capillary was rinsed and sealed, the waste liquid was discarded, and all equipment was shut down step by step. The column temperature was strictly controlled at 25 ℃, the detection wavelength was fixed at 220 nm, the injection conditions were an injection height of 10 cm, an injection time of 5 s, and the separation voltage was adjusted to 10 kV. The run buffer was 10 mM phosphate buffer (containing 55% acetonitrile, pH=9.5). All experimental solutions (including the sample) were filtered through a 0.45 μm organic phase filter membrane before use. Resolution R s The calculation formula is as follows:
[0112]
[0113] Where t1 and t2 are the retention times of the two enantiomers, and w1 and w2 are the half-peak widths of the two enantiomers.
[0114] Thanks to its intrinsic helical chiral pore framework, the (Λ)-TAPM-TPA COF prepared in this invention exhibits excellent recognition ability for a variety of chiral drug molecules. For example... Figure 8 As shown, experiments have demonstrated that this modified capillary column can efficiently distinguish multiple chiral analytes, and all racemic drugs achieved ideal baseline separation: amlodipine resolution R... s =1.69, Propranolol R s =2.27, Metoprolol Rs =2.16, Chlorpheniramine R s =1.89, Clenbuterol R s =1.76, Terbutaline R s =1.86, Verapamil R s =1.65, Isoproterenol R s =2.07.
[0115] The results of the 1st, 10th, 15th, 20th, and 50th consecutive injections of R / S-amlodipine are as follows: Figure 9 As shown, the separation performance of the open-tube capillary electrochromatographic column showed no significant decline after 50 consecutive injections. This capillary column exhibits excellent general chiral recognition performance and can efficiently separate various chiral drug molecules with different structures. This synthetic strategy fully demonstrates the application prospects of chiral-induced COF materials in chromatographic separation technology.
[0116] Example 4: Elucidation of the mechanism of chiral induction and molecular stereorecognition based on density functional theory wavefunction analysis
[0117] This embodiment analyzes the mechanism of COF(Λ)-TAPM-TPA induced by the chirality of L-(+)-tartaric acid (the molar ratio of tartaric acid carboxyl groups to TAPM amino groups is 1:5) prepared in Example 1. All calculations were performed using the Gaussian16 C01 package. All calculations used a Becke three-parameter hybrid exchange functional combined with a Lee-Yang-Parr correlated functional (B3LYP), along with Grimme D3 dispersion correction and a Becke-Johnson damping function (DFT-D3BJ). Geometric optimization and frequency calculations used the 6-31G (d,p) basis set. Frequency calculations verified that the optimized structure had no imaginary frequencies, proving that all optimized configurations were true minima on the potential energy surface. Single-point energy calculations used the more precise 6-311G (d,p) basis set. To simulate the water / acetonitrile mixed solvent system in the experiment, an implicit solvent model (SMD) was used, and custom dielectric parameters were defined: the static dielectric constant ε was set to 60.543, and the optical dielectric constant ε∞ was set to 1.7904. The binding energy between molecule A and molecule B was calculated using the following formula: Ebind = Ecomplex(AB) - (EpartA + EpartB). The electrostatic potential (ESP) distribution was plotted using the Multiwfn program and VMD visualization software, and a visualization analysis of weak interactions was performed based on the independent gradient model (IGMH) partitioned by Hirshfeld.
[0118] 1. (Λ)-TAPM-TPA COF chiral memory growth mechanism
[0119] The formation process of (Λ)-TAPM-TPA is similar to the growth process of chiral TAPM-TPA under homogeneous conditions. In the initial stage of (Λ)-TAPM-TPA growth, monomers gradually polymerize to form soluble oligomers; subsequently, nucleation occurs to form chiral COF microcrystals with undetermined structure and size, with the smallest unit potentially being a single six-membered macrocycle. Based on this, this embodiment proposes a (Λ)-TAPM-TPA formation mechanism model (e.g., Figure 10 (As shown). In this invention, L-(+)-tartaric acid is used as an equivalent TPA end-capping agent, which can reversibly form imine bonds with TAPM. The resulting imine intermediate cannot participate in COF polymerization. As a competing ligand, L-(+)-tartaric acid prolongs the nucleation induction period, inhibits rapid precipitation, and introduces chiral steric hindrance during the stacking process. Subsequently, TPA replaces L-(+)-tartaric acid in the scaffold growth, the original active sites retain chiral memory, and ultimately induce the formation of a twisted scaffold structure.
[0120] 2. Density functional theory-assisted analysis of enantioselective identification of molecular origins
[0121] The excellent chiral resolution performance of this capillary electrochromatographic system is essentially determined by the intrinsic enantiomeric recognition ability of the chiral stationary phase (Λ)-TAPM-TPA. The key is the introduction of L-(+)-tartaric acid as a chiral inducer during the synthesis stage, which endows the material with a specific chiral microenvironment, enabling it to exhibit significantly different binding affinities with the two enantiomers of amlodipine. To reveal the source of selectivity at the molecular level, this invention utilizes molecular docking, density functional theory calculations, and multiwave function analysis to explore the host-guest interaction between (Λ)-TAPM-TPA and R- / S-amlodipine.
[0122] First, molecular docking simulations were conducted to screen stable binding conformations and evaluate binding thermodynamics. A swarm intelligence docking algorithm was then used to fully sample multiple potential adsorption modes, and geometric optimization was performed on the low-energy conformation. The calculation results show that the lowest binding energy between S-amlodipine and (Λ)-TAPM-TPA is -27.83 kcal·mol⁻¹. -1 It can spontaneously form stable host-guest complexes through various non-covalent interactions; in comparison, R-amlodipine has a minimum binding energy of -33.20 kcal·mol⁻¹. -1 This indicates that R-amlodipine has a stronger affinity for the chiral recognition site of (Λ)-TAPM-TPA. The significant difference in binding energies between the two confirms that this chiral framework possesses excellent enantioselective binding tendency. To further elucidate the intrinsic binding mechanism, density functional theory single-point energy calculations and subsequent wavefunction analyses were performed on (Λ)-TAPM-TPA, the two enantiomers, and their assembled complexes. The electrostatic matching effect was assessed using the electrostatic potential (ESP) distribution characteristics, and the corresponding ESP diagram is shown below. Figure 11As shown in a and b, the electrostatic potential values of the (Λ)-TAPM-TPA chiral framework recognition site are relatively high, while the overall electrostatic potential of the amlodipine molecule is relatively low. From the perspective of electrostatic complementarity, the potential difference is conducive to the tight binding of the amlodipine enantiomer and the host chiral fragment. More importantly, there is a significant difference in the electrostatic matching degree between the two diastereomeric complexes: the R-amlodipine / (Λ)-TAPM-TPA binding interface has an excellent positive and negative electrostatic potential matching degree, generating a strong electrostatic attraction and significantly stabilizing the complex structure; the S-amlodipine complex system has poor electrostatic complementarity and lacks effective electrostatic interactions, which is consistent with the results of higher binding energies. Furthermore, the independent gradient model (IGMH) based on Hirshfeld partitioning is used to intuitively characterize the type, distribution, and strength of weak intermolecular interactions, clarifying the microscopic nature of chiral recognition (such as...). Figure 12 As shown in the image). IGMH visualization results show that the interaction regions of both complexes are dominated by green isosurfaces, proving that the host-guest interactions in both systems are dominated by van der Waals dispersion forces, with no significant strong hydrogen bonds or steric repulsion effects; however, there are significant differences in the spatial contact state and interaction distribution of the two complexes: the isosurfaces of the S-amlodipine complex are continuous and dense, indicating full and close contact between the host and guest; the isosurfaces of the R-amlodipine complex are relatively scattered and discontinuous, with a smaller effective contact area between the host and guest. Meanwhile, the IGMH scatter plot (as shown in the image)... Figure 13 As shown in the figure, the S-amlodipine system exhibits stronger and more concentrated interactions, while the R-amlodipine system shows weaker and more dispersed interactions. This indicates that S-amlodipine has a better conformational match with the chiral host and exhibits stronger dispersive interactions.
[0123] In summary, the enantioselective recognition behavior of (Λ)-TAPM-TPA is determined by the synergistic effect of electrostatic interactions regulated by molecular stereoconfiguration and van der Waals dispersion forces: R-amlodipine achieves higher overall binding stability due to its electrostatic complementarity; S-amlodipine only excels in spatial stacking and dispersion interactions, but its electrostatic matching ability is insufficient. The competitive balance between the two types of non-covalent interactions ultimately determines the difference in binding affinity between the chiral stationary phase and the two enantiomers. This invention systematically elucidates the molecular-scale chiral resolution mechanism of the (Λ)-TAPM-TPA-modified capillary electrochromatography system through theoretical simulation, explaining its excellent practical resolution performance and providing reliable theoretical guidance and feasible design strategies for the directional construction and performance optimization of novel and efficient chiral stationary phases.
Claims
1. A method for preparing a capillary electrochromatographic open column based on chiral-induced covalent organic framework modification, characterized in that, Includes the following steps: (1) A capillary with exposed silanol groups on its wall was obtained by sequentially passing a fused silica capillary through a sodium hydroxide solution and a hydrochloric acid solution. A capillary with amino-modified walls was obtained by injecting a 3-aminopropyltriethoxysilane solution into a capillary with exposed silanol groups and incubating it under sealed conditions at a constant temperature. A glutaraldehyde aqueous solution was then injected into the amino-modified capillary and reacted at room temperature to obtain a capillary with spacer arms covalently connected to the wall. (2) Dissolve terephthalaldehyde and tetra(4-aminophenyl)methane in a solvent and sonicate to obtain a reaction system; add L-(+)-tartaric acid aqueous solution to the reaction system and mix evenly, then quickly pump into a capillary tube covalently connected with a spacer arm, and seal and react at a constant temperature; after the reaction is completed, cool to room temperature, rinse the capillary tube with acetonitrile, and dry with high-purity nitrogen to obtain the capillary electrochromatographic open column.
2. The method according to claim 1, characterized in that, The molar ratio of terephthalaldehyde to tetra(4-aminophenyl)methane is 2:
3.
3. The method according to claim 1, characterized in that, The solvent includes any one of 1,4-dioxane, dimethyl sulfoxide, and N,N-dimethylformamide.
4. The method according to claim 1, characterized in that, The ratio of the molar number of carboxyl groups in tartaric acid to the molar number of amino groups in tetrakis(4-aminophenyl)methane in the L-(+)-tartaric acid aqueous solution is 1:5~10.
5. The method according to claim 1, characterized in that, The sealed, constant-temperature reaction takes 4 to 8 days.
6. The method according to claim 1, characterized in that, The constant temperature is 80 ℃.
7. A capillary electrochromatographic open column based on chiral-induced covalent organic frame modification, characterized in that, It is prepared by the method described in claim 1.
8. The application of the capillary electrochromatographic open column of claim 7 in the separation of chiral drug molecules, characterized in that, The chiral drug molecules include one or more of amlodipine, propranolol, metoprolol, chlorpheniramine, clenbuterol, terbutaline, verapamil, and isoproterenol.
9. The application according to claim 8, characterized in that, It includes the following steps: (1) Install the capillary electrochromatographic open column as described in claim 7 into the electrophoresis instrument, and connect one end to the ultraviolet detector to complete the installation; (2) After installation, rinse the activated capillary with running buffer; (3) The chiral drug molecule to be tested is dissolved in a water-methanol mixture and introduced into an activated capillary. After injection, separation is achieved by applying a separation voltage. The ultraviolet detector captures the absorbance signal and generates an electrophoresis pattern in real time, thereby realizing the separation and detection of chiral drug molecules.
10. The application according to claim 9, characterized in that, The running buffer comprises a 5-15 mM phosphate buffer solution containing 50%-60% acetonitrile, the pH of which is 9-10; the water-methanol mixture has a water-to-methanol volume ratio of 1:1; and the final concentration of the chiral drug is 0.1-0.9 mg / mL. -1 The separation voltage is 5~15 kV; the injection height is 5~10 cm, and the injection time is 2~9 s; the capillary column temperature is kept constant at 20~30 ℃ throughout the separation and detection process.
